Towards an integrative model of C4 photosynthetic subtypes insights from comparative transcriptome analysis of NAD-ME, NADP-ME, and PEP-CK C4 species - Bräutigam, Andrea (Journal of experimental botany, 2014)
© The Author 2014. Published by Oxford University Press on behalf of the Society for Experimental Biology.